(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
out in english speech training for students of the english language education study program to developing english speech skills. Using a qualitative descriptive research method. Data collection is based on observation, interviews and documentation. The results of the study found that in speech training for english students at Panca Sakti University, Bekasi. They had implemented the SIUUL model well according to the stages and provisions of the method. Based on the use of the SIUUL method in developing english speech skills, it can be concluded that this methods quite effective in helping students developing their english speech skills. The SIUUL method promotes interactive and collaborative learning principles, so as to increase participant motivation and participation in the learning process. However, as is the case with other learning methods in developing english speech skills depends of factors such as the level of motivation of the students, the quality of the instructor’s teaching and the availability or adequate resources and technological support. Therefore, it is important for students of the SIUUL method to pay attention these factors in order to maximize learning potential and achieve the desired results.